2018
DOI: 10.3145/epi.2018.ene.05
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of title words for journal articles and Wikipedia pages: Coverage and stylistic differences?

Abstract: Mike Thelwall leads the Statistical Cybermetrics Research Group at the University of Wolverhampton, UK. He has developed and evaluated free software and methods for systematically gathering and analysing web and social web data, including for sentiment analysis, altmetrics and webometrics, and for Mendeley, Twitter, YouTube, Google Books, blogs and the general Web. He also conducts evaluation exercises for large organisations using web data, including for various divisions within the United Nations and Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Thus, overall, site nationality (Table 1) is enough to explain the low position of most of the sites. A similar issue has been observed within another repository of knowledge, Wikipedia, which has greater coverage of topics relevant to an English-speaking audience despite its international variants Sud, 2018).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, overall, site nationality (Table 1) is enough to explain the low position of most of the sites. A similar issue has been observed within another repository of knowledge, Wikipedia, which has greater coverage of topics relevant to an English-speaking audience despite its international variants Sud, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…WikiProject Medicine within Wikipedia is a related project to ensure the accuracy of medical pages (Heilman et al, 2011). Some articles have also assessed evidence for political or gender bias (Gauthier;Sawchuk, 2017;Stahel, 2018), or discussed potential coverage gaps (Luyt, 2018;Sud, 2018).…”
Section: Wikipediamentioning
confidence: 99%
“…The next step was the standardisation of categories across databases to unify the analysis. Standards in bibliometric research understand that the ideal practice is to use a single type of database where indicators are already standardised [24]. In our case, this was not possible due to the high atomisation and specialisation of the databases; however, no relevant metadata gaps were found, and differences in metadata were mitigated by selecting higher-quality metadata, such as the number of citations of a publication (cited or cited count).…”
Section: Methodsmentioning
confidence: 98%

The Impact of Biases on Health Disinformation Research

Peñafiel-Saiz,
Echegaray-Eizaguirre,
Perez-de-Arriluzea-Madariaga
2024
Societies
“…For example, Kaur, Lee, Tiew, and Sen (1997) have compared titles of research articles with textbooks. Similarly, Thelwall and Sud (2018) compared research article titles with Wikipedia page titles and found that Wikipedia page title rarely use synonyms of "analyzing." In regard to the impact studies of titles, Hudson (2016) found that the use of a colon has a negative impact on 16 disciplines whereas five disciplines show positive impacts.…”
Section: Previous Studiesmentioning
confidence: 99%